PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT ACTIVITY OF EUCALYPTUS LEAF ESSENTIAL OIL - Ahmed, Rozhgar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The genus Eucalyptus belongs to the Myrtaceae family and is a large tree with several uses due to its content of some useful active components. These phytochemical components have been used for many years to treat various illnesses. The extraction process and identification of these components are essential points to maximize and develop the level of content. The extraction of essential oil from the eucalyptus leaf was investigated using hydrodistillation based on four locations in the Sulaimani region. Furthermore, the antioxidant activity was also studied using a free radical scavenging assay. The highest essential oil content was noticed in Qara Dagh in both fresh and dry leaves (2.33% and 4.67%), while the lowest level of fresh leaves was detected in Sharbazher (1.27%) and dry leaves in Kalar (2.40%). Fifty-eight chemical components were identified in eucalyptus essential oil using GC-MS analysis.  Eucalyptol and α-pinene were found to be major components at all locations. The greatest amounts of eucalyptol and α-pinene were observed in Qara Dagh (52.309±0.967% at 6.163 min) and (14.652±0.194 % at 3.703 min), respectively. The essential oil scavenging effect indicated that the Sharbazher location gave a maximum scavenging effect of 60.156%. Compared to the lowest scavenging effect, which was achieved by the Qara Dagh location with a value of 47.613%.